2005
DOI: 10.2747/1538-7216.46.5.364
|View full text |Cite
|
Sign up to set email alerts
|

Shades of Orange: The Electoral Geography of Ukraine's 2004 Presidential Elections

Abstract: Two American geographers and noted specialists on the electoral geography of post-Soviet Russia and Ukraine describe and analyze the three rounds of Ukraine's pivotal and highly contested presidential elections in late 2004. In an effort to shed light on the underlying demographic and socio-economic correlates of the vote (e.g., age, income, urban/rural residence, language/ethnicity), the authors pay special attention to changes among the rounds, providing background to widespread allegations of electoral frau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…They concluded that taken together in a multiple regression model (which they did not present), the single most powerful variable in terms of explaining regional differences in electoral preference for Yushchenko or Yanukovych was the 'Ukrainian Russophone measure, followed by the industrial and mining work force variable, and then by the change in income variable, which together generate an R 2 of .8632; that is, these three measures explain virtually all the variation in the regional voting patterns at this level'. 24 In other studies, the ethno-linguistic and urban -rural attributes of the Orange supporters and their opponents seem to emerge also as the only clearly distinctive difference between the two camps, with the Ukrainian speakers and the countryside coming out disproportionately in favour of Yushchenko (and the opposite holds). 25 In the following sections, these competing explanations will be tested in an attempt to resolve the controversy.…”
Section: Societal Cleavages and Partisan Conflict: Hypotheses About Tmentioning
confidence: 93%
“…They concluded that taken together in a multiple regression model (which they did not present), the single most powerful variable in terms of explaining regional differences in electoral preference for Yushchenko or Yanukovych was the 'Ukrainian Russophone measure, followed by the industrial and mining work force variable, and then by the change in income variable, which together generate an R 2 of .8632; that is, these three measures explain virtually all the variation in the regional voting patterns at this level'. 24 In other studies, the ethno-linguistic and urban -rural attributes of the Orange supporters and their opponents seem to emerge also as the only clearly distinctive difference between the two camps, with the Ukrainian speakers and the countryside coming out disproportionately in favour of Yushchenko (and the opposite holds). 25 In the following sections, these competing explanations will be tested in an attempt to resolve the controversy.…”
Section: Societal Cleavages and Partisan Conflict: Hypotheses About Tmentioning
confidence: 93%
“…Fearful of loss of access under Yushchenko (in the words 7 that are not either strongly pro-Yushchenko or strongly pro-Yanukovich. Yushchenko's political base was in the most western, historically Hapsburg part of the country (Clem and Craumer, 2005), and he owed nothing to the men who had financed the campaign against him. Upon taking power, Yushchenko named Yulia Tymoshenko, an oligarch-turned-populist who was one of Ukraine's savviest political operators, to head a short-lived government that was notable for the absence of easterners.…”
mentioning
confidence: 99%
“…3 The episode highlighted for the Ukrainian leadership the dangers of isolation from the West. Kuchma made some progress in restoring relations with the United States, but that was largely undone by the government's manipulation of election results in the second round of the presidential election in November 2004 (e.g., for background, see Clem and Craumer, 2005). The fraudulent count triggered the Orange Revolution.…”
Section: Ukrainian Foreign Policy In the Kravchuk And Kuchma Yearsmentioning
confidence: 98%